Disciplining and Screening Top Executives - Silvia Dominguez Martinez; Otto H. Swank; Bauke Visser (Tinbergen Institute, 2006)
Boards of directors face the twin task of disciplining and screening executives. To perform these tasks directors do not have detailed information about executives' behaviour, and only infrequently have information about the success or failure of initiated strategies, reorganizations, mergers etc. We analyse the nature of (implicit) retention contracts boards use to discipline and screen executives. Consistent with empirical observation, we find that executives may become overly active to show their credentials; that the link between bad performance and dismissal is weak; and that boards occasionally dismiss competent executives.
Keywords: G30; G34; 330; board of directors; turnover; retention contracts; selection; moral hazard; empire building